Investigation of The Effect of Temperature and Contamination on Properties of Saturated Salt-Base mud - Abdul Hussien, Hassan A.; Salih, Mohammed S. (Journal of Petroleum Research and Studies, 2023)
The most difficult challenge that can be encountered when drilling a salt section is the difficulty of controlling the change in drilling fluid properties. In addition, the challenging geological environment was encountered. , creep behavior, slim hole drilling in salt formation have a few traits: high soluble, wash out salt section (1). The treatment did by using drilling mud that inhibits changes and is resistant to contaminants. Sodium chloride and potassium chloride brine were used to create a new mud for discussing this research, following up on changes in the properties of the new mud, simulating the conditions of Salt section (12.25'' hole) in the Noor oil field. Moreover, In this investigation studied the effect of temperature and contaminants such as salt, shale and anhydrite on new mud properties (Rheological properties, Filtration, PH with Different concentrations of Kcl & Nacl. The results indicate that the dissolution of salt formation decreases with increasing KCl concentration up to 5% for saturating NaCl salt. This reduces the contaminant impact and increases the stability of mud characteristics.